The daily calcium profile in patients with chronic hypoparathyroidism depending on different 25(OH) vitamin D level - E. V. Kovaleva; A. K. Eremkina; A. R. Elfimova; A. M. Gorbacheva; N. G. Mokrysheva (Ожирение и метаболизм, 2024)
BACKGROUND: Chronic hypoparathyroidism is a relatively rare disease, which usually treated active forms of vitamin D and oral calcium supplements. Supplementation with native vitamin D can be useful both for achieving «non-skeletal» effects of vitamin D and for a more stable serum calcium profile.AIM: The aim of this study was to estimate the daily serum calcium and 24-hour urine calcium levels depending on different 25(OH) vitamin D values in patients with chronic hypoparathyroidism on treatment of active forms of vitamin D and calcium supplements.MATERIALS AND METHODS: Forty patients with chronic hypoparathyroidism were involved in the study. All patients were divided in two groups, matched on sex and age, according to the median level of 25(OH) vitamin D in the total group.RESULTS: There were no significant differences between groups by total, albumin-adjusted serum calcium levels and urine calcium excretion. Patients with serum 25(ОН) vitamin D level ≥ 35 ng/ml had significant tendency to achieve more often the target levels of total serum calcium during the day (128 vs. 149 measurements during the day, p=0.049, χ2). However, this tendency disappeared for albumin-adjusted serum calcium levels (p=0.517, χ2). There frequency of hypercalcemia by albumin-adjusted serum calcium in the group of patients with 25(ОН) vitamin D ≥ 35 ng/ml (p=0.006, χ2) was significantly lower, but not for total serum calcium (a trend, p=0.042, χ2). As regards hypocalcemia, there were no significant differences by albumin-adjusted serum calcium (p=0.581, χ2) and it tends to lower frequency by total serum calcium (p=0.023, χ2).CONCLUSION: The additional administration of native vitamin D in patients with chronic hypoparathyroidism may have some advantages, related to the general concept of worldwide vitamin D deficiency and better disease control.